Child nutrition to new stage in China: evidence from a series of national surveys, 1985-2015 - Xin-Nan Zong; Hui Li; Ya-Qin Zhang; Hua-Hong Wu (BMC, 2019)
Abstract Background Both child under- and over-nutrition are major global public health challenges. We aimed to examine thirty-year trends in physical growth, under- and over-nutrition in Chinese urban and suburban children between 1985 and 2015, and discuss implications for child health programmes. Methods A total of 610,785 urban and suburban children from birth to 7 years of age were collected from a series of large-scale national surveys in China. Height, weight and body mass index (BMI) Z-scores and prevalence of stunting, underweight, wasted and possible risk of overweight, overweight and obesity were calculated according to the World Health Organization (WHO) 2006 growth standards. The trends in the prevalence were tested across different survey years by Cochran-Armitage trend test. Results Rapid secular growth trend was observed in China over the past 30 years, but the trend showed a slowing sign in urban children in recent 10 years. The growth level of Chinese urban and suburban children surpassed the WHO 2006 growth standards in 2015. Between 1985 and 2015 the stunting, underweight and wasted prevalence decreased from 12.21, 4.44, 1.68 to 0.97%, 0.59, 0.87% for children under 5 years and from 12.69, 10.02, 3.41 to 0.42%, 0.67, 2.17% for children aged 5- < 7 respectively; the possible risk of overweight prevalence increased from 6.51 to 12.57%, overweight from 0.70 to 3.48% and obesity from 0.17 to 0.86% for children aged 2- < 7 and the increasing rates of overweight and obesity prevalence in suburban children first outnumbered urban children in recent 10 years. The overweight prevalence overtook the wasted or underweight in children aged 2- < 7 in 2005 and onward. Conclusion Slowing secular height trend and overweight prevalence overtaking the wasted or underweight suggested child nutrition and health strategies should adjust swiftly and deliberately from primarily reducing under-nutrition prevalence to controlling rapid weight gain and promoting integrated early development.